Gambaran Pengetahuan Tentang “Ciber Oil” (Cinnamomum Burmannii Dan Zingiber Officinale) Untuk Mengurangi Keluhan Dismenore Pada Remaja Di Smkn 2 Malang - Nyna Puspita Ningrum; Solichatin; Reza Rachmawati; Niken Larasati (SNHRP, 2023)
According to WHO, in the world the incidence rate is quite high. The incidence of dysmenorrhoea in young women on average: 16.8 persen -81persen. The average in European countries menstrual pain occurs in women 45-97 persen. The lowest Bulgarian prevalence is 8.8 persen., the highest is 94 persen in Finland. The highest prevalence of dysmenorrhea is often found in adolescent girls, which is estimated: 20-90 persen. About15 persen of adolescents have severe dysmenorrhea. The purpose of this study was to determine the knowledge of students about Ciber Oil to reduce menstrual pain in students of SMKN 2 Malang.Method in this research Quantitative descriptive research with survey. The sample in this study were 74 female students of SMKN 2 Malang Sampling technique with Purposivesampling. Data analysis using frequency distribution.The results of this study are then given an interpretation based on the variables studied based on the criteria of good, adequate and insufficient. The results of this study indicate that students of SMKN 2 Malang have knowledge of Ciber Oil for Menstrual Pain Reduction, the overall knowledge is good with a total of 74 people (100.0 persen).Suggestion: For female students to further improve their knowledge about health, especially about ginger prebiotics to reduce menstrual pain, by practicing how to process them every month with herbs.